Report of the 22nd planning conference on integrated pest management - International Potato Center; International Potato Center (CIP) (Lima, Peru : International Potato Center (CIP), 1984)
The purpose of the conference was to identify those priority components of Integrated Pest Management for which CIP has a comparative advantage to research
Includes bibliographical references.
osc 15/04/2019
Loans
Keywords: Pest control; Agriculture; Potato